The impact of ESA teaching sequence on EFL university students’ speaking fluency and classroom interaction - Abdul Ayiz; Kurniawan Yudhi Nugroho; Benni Ichsanda Rahman Hz; Nurussyfa Luthfia Kholifah; Yuko Taniguchi (Journal of Research in English Language Teaching and Linguistics, 2026)
The ESA (Engage, Study, Activate) teaching sequence introduced by Jeremy Harmer offers a flexible, recursive alternative to linear instructional models such as Presentation-Practice-Production (PPP). However, empirical evidence regarding its effectiveness for speaking fluency and classroom interaction, particularly in university EFL contexts, remains relatively limited. This quasi-experimental study investigated the impact of the ESA teaching sequence on speaking fluency and classroom interaction among university EFL learners, comparing it to conventional PPP instruction. Sixty first-year undergraduate students from two intact classes participated in an eight-week intervention. The control group (n = 30) received PPP instruction, while the experimental group (n = 30) received ESA instruction following the boomerang variation (Engage → Activate → Study → Activate). Speaking fluency was measured through speech rate (syllables per minute) and pause frequency (pauses per 100 syllables) using picture-cued speaking tasks administered as pretest and posttest. Classroom interaction was measured through systematic observations at Weeks 2, 4, 6, and 8, capturing student talk time, student-initiated turns, and negotiation episodes. The ESA group demonstrated statistically significant improvements in speech rate and pause frequency with large effect sizes, whereas the PPP group showed non-significant gains. Regarding classroom interaction, the ESA group exhibited substantially higher student talk time, more student-initiated turns, and more numerous negotiation episodes compared to the PPP group at post-intervention. These findings provide strong evidence within this context that the ESA teaching sequence enhances speaking fluency and promotes more balanced, learner-centered classroom interaction in university EFL contexts. Pedagogical implications include reallocating class time to communicative activities, reducing teacher talk time, delaying correction during fluency tasks, and explicitly teaching interactional strategies during the Study phase. Future research should examine long-term retention, accuracy outcomes, and replication across diverse educational settings.